Modulation of antiviral genes by African swine fever isolates of diverse virulence - Franzoni, Giulia; Mura, Lorena; Zinellu, Susanna; Sanchez-Cordon, Pedro J.; Pedrera, Miriam; Dei Giudici, Silvia (Frontiers in Veterinary Science, 2025)
African swine fever virus (ASFV), the aetiological agent of a devastating swine disease, has developed several strategies to replicate in porcine macrophages, its main target cells. In this work, we investigated the expression of 84 antiviral genes in macrophages infected with the virulent strain 26544/OG10 or the attenuated strain NH/P68. Infection with both strains caused an early activation of antiviral defenses, with up-regulation of RNA-sensing molecules and interferon-stimulating genes. However, as viral replication progresses, down-regulation of key inflammatory genes was observed, especially during infection with NH/P68, suggesting an impairment of macrophages' inflammatory response. Data generated provide a better portrait of ASFV immune evasion strategies.